(untitled) (LEARNing Landscapes, 2020)
In this interview, Joe Norris reflects on his early experiences with performance and how he became involved with collective creations and playbuilding. His work has led him to develop and implement qualitative research methods using playbuilding. In his role as artistic director of Mirror Theatre, he has been the driving force behind numerous plays that inspire social change. He shares candid observations about the challenges of doing performative work and gives advice for educators wishing to pursue this kind of work.